PENGARUH INTEGRASI NIK-NPWP DAN PENERAPAN E-FILLING TERHADAP KEPATUHAN WAJIB PAJAK DALAM PELAPORAN SURAT PEMBERITAHUAN (SPT) TAHUNAN ORANG PRIBADI - Surachman, Surachman; Sembiring, Evi Dora; Rahayu, Noviyani (Indonesian Journal of Economy, Business, Entrepreneuship and Finance, 2024)
This research aims to determine the effect of NIK-NPWP integration and the implementation of e-filling on taxpayer compliance in individual annual tax returns for taxpayers registered at KPP Pratama West Serang. The research method used in this research is quantitative correlational with survey methods. The population used was taxpayers who were registered at KPP Pratama West Serang and used incidental sampling techniques, totaling 180 samples. The data used is primary data by distributing questionnaires within the West Serang Pratama KPP environment and using a Likert scale. The test tool used is SPSS version 26 and the methods used are descriptive analysis, classical assumption test, coefficient of determination test, hypothesis testing, and multiple linear regression. The research results show that both partially and simultaneously, NIK-NPWP integration and the implementation of e-filling have a positive and significant effect on taxpayer compliance in reporting individual annual tax returns